AMIL PROFESSIONALISM AND THE ROLE OF ZAKAT IN THE ECONOMIC RECOVERY OF THE PEOPLE DURING THE COVID 19 PANDEMIC - Arie Sulistyawan (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2022)
Amil's professionalism and the role of zakat in the economic recovery of the people during the Covid 19 pandemic is the purpose of this research. Qualitative method with the type of library research used in this study, because the data includes experiencewriters and literature related to the research. The case of the Covid 19 Pandemic, which has never been felt in this country, has made Amil zakat move quickly to distribute zakat for the welfare of the community and their economic applications.zakat potential has not been reached, at least zakat able to show positive things for the people who find it, that's the result of this research. As a result of the COVID-19 pandemic, of course the principles of professional zakat management institutions and the positive role of other parties that are maximally needed to achieve a higher realization of zakat so that they can help people's economy. So that the potential for zakat can be maximized and increased, several things are needed: must be improved, namely regarding, digitalization of zakat, socialization, and innovation.